Properties of chicken feather fiber-filled low-density polyethylene composites: The effect of polyethylene grafted maleic anhydride - Supri, Abdul Ghani, Prof. Madya Dr. (Taylor and Francis Group, LLC., 2014)
Link to publisher's homepage at http://www.taylorandfrancisgroup.com/